ChemInform Abstract: Air‐Stable Gold Nanoparticles Ligated by Secondary Phosphine Oxides for the Chemoselective Hydrogenation of Aldehydes: Crucial Role of the Ligand. Issue 34 (26th August 2014) - Cano, Israel; Chapman, Andrew M.; Urakawa, Atsushi; van Leeuwen, Piet W. N. M.
Abstract The synthesis of novel air‐stable gold nanoparticles employing tert‐butyl(naphthalene‐1‐yl)phosphine oxide as supporting ligand and its characterization using a wide range of techniques is reported.